Program Bank Sampah Dan Pendapatan Keluarga Di Kecamatan Ciputat Timur Kota Tangerang Selatan - Aminudin Aminudin; Djoko Manggolo (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2017)
The purpose of this research is; first to examine and analyze the impact of the Garbage Bank program on the income level of customers’ families of the Waste Bank and second is to Analyze the satisfaction of the customers of the Garbage Bank customers with the additional income by saving the garbage at the Bank Trash. The object of the research was conducted at the Customers of Garbage Banks located in East Ciputat Subdistrict consisting of six urban villages namely Cempaka Putih, Pondok Ranji, Rengas, Rempoa, Cireundeu and Pisangan, with garbage bank counted as 10 garbage banks, by spreading kusioner as many as 50 sample people. Test The first hypothesis shows that it is concluded no effect Variables Program Garbage Banks Variable Level Income Family Customer Bank Trash. The second hypothesis test shows that, it is concluded no effect Variable Satisfaction of Customers of Waste Banks against Variable Level of Income of Customer Family of Garbage Bank. First correlation test. The relationship between the bank waste program with the addition of family income is very weak. The second correlation test shows that the relationship between customer satisfaction of garbage bank with the amount of saving of waste bank is very weak too.